RESIDENTIAL LIFESTYLES AND ITS RELATIONSHIP WITH RESIDENTIAL ENVIRONEMNT EVALUATION: A CASE STUDY OF SAGA CITY, JAPAN - J. Ge; K. Hokao (International Association of Lowland Technology, 2004)
With the diversification of personal sense of values, as weel as the abundance of lifestyles, people's demands on residential environment are becoming more and more abundant. In this paper, by the case study of Saga City, the approaches to grasp the residential lifestyles are analyzed at first. Then, through each approach, the residential lifestyle patterns were classified, and the characteristics of each pattern were grasped. Furthermore, the relationship between residential lifestyle and residential environment evaluation are analyzed, and the suitable models for various styles were established. The results not only can be used as the rudimentary data for the improvement and development of residential environment, the mmethodology of considering residential lifestyle can also bring about a new and useful viewpoint for the further research of residential environment evaluation.